A Pragmatic Study of Identity Representation in American Political Speeches (Journal of the College of Education for Women, 2022)
Identity is an influential and flexible concept in social sciences and political studies. The basic sense of identity is looking for uniqueness. In one sense, it is a sign of identification with those we assume they are similar to us or at least in some significant ways they are so. Globalization, migration, modern technologies, media and political conflicts are argued to have a crucial effect on identity representation in terms of the political perspectives specifically in the United States of America. This paper endeavors to investigate how American politicians represent their identities in speeches delivered in different periods of time namely from 2015 to 2018 in terms of the pragmatic paradigm. Three randomly selected speeches by famous American politicians are chosen for the analysis. This paper aims to answer these questions: What are the possible types of identity that are represented in the American political speeches? What are the pragmatic phenomena utilized to manifest identity in the contexts under investigation? Which pragmatic strategies are highly made use of in representing identity in the contexts under scrutiny? Data analysis shows that different types of identity representations appear in the data like the national and political identity, among others. Speech acts, reference, impoliteness and maxim breaching are the pragmatic phenomena that are utilized in the manifestation of identity in the American political speeches. The first two are the most utilized ones among the other pragmatic theories.